(untitled) (The Batuk, 2020)
Television advertisement has become a permanent means of delivering product and service messages to all upper and middle class households. The study aims at examining effectiveness of TV advertisement. Online survey with structured questionnaire was conducted through the various social media. Sample sizes of 150 people are selected for the study by using random sampling method to collect the data to avoid biasness in the selection process. The study found that the people are more attracted toward the use of internet. Most people tend to spend less time watching television and more time on internet and other activities. It is concluded that there is lack of effectiveness of television advertisements in modern era.